Correlation and Comparison of Tongue Print and Lip Print with Blood Group among Dental Students of Jharkhand - Nishad Gawali; Ankur Bhargava; Sonal Saigal; Prajakta Khelkar; Ayushi P. Mangulkar; Chetan A. Fukate (Wolters Kluwer Medknow Publications, 2024)
Aim: This research set out to determine whether or not there was a connection between the types of lip print patterns found on people's lips and their blood types, as well as between the tongue print patterns found on people's tongues and their blood types. Material and Methods: One hundred and three females and 51 males participated in our research after providing informed permission after hearing about the study's objectives and potential therapeutic applications. Results: One hundred and three females and 51 males participated in our research after providing informed permission after hearing about the study's objectives and potential therapeutic applications. Conclusion: While we did find gender differences in lip print and tongue pattern distribution and blood group, our research did not find statistically significant outcomes between these variables.